Cutaneous epitheliotropic lymphosarcoma in a captive white catfish (Ameiurus catus Linnaeus). Issue 7 (27th April 2022) - Heniff, Ashlyn C.; Chen, Laura R.; Christiansen, Emily F.; Harms, Craig A.; Law, Jerry M.; Legner, Christian; Linder, Keith E.
Abstract: A wild caught white catfish ( Ameiurus catus Linnaeus) developed multiple cutaneous masses. Cytology revealed neoplastic lymphocytes and microscopy confirmed dermal infiltration with epitheliotropism in the epidermis, oral mucosa, and cornea, without internal organ involvement. Transmission electron microscopy did not identify viral particles. Histopathology supported cutaneous epitheliotropic lymphosarcoma, a condition most commonly reported in mammals. This is the first reported case of cutaneous epitheliotropic lymphosarcoma in an ictalurid and one of the few published cases of this condition in any fish species.